The Evolution of Modern Architecture Style in Context of Postcolonial Campus - Mean Pisei; Ikaputra Ikaputra (Departement of Architecture, Universitas Islam Indonesia, 2021)
The development of Indonesian architectures in the post-colonial era were the phase of new experiment and ideas that gave a birth to the awareness and spirit of exploring nation identity. Universitas Gadjah Mada is recognized as a post-colonial and the oldest national campus founded in 1949 in Yogyakarta. This paper aims to investigate the evolution of modern movement in the sense of campus architecture. Case study material is drawn mainly from post-colonial campus architecture at the central zone of Universitas Gadjah Mada. The method used is a qualitative methodology in which data is obtained from literature reviews and field observations. The development of modern architecture theories and styles have been studied through the case study. The finding of this study showed that socio-political transition of the old order, the new order, and present era, and also personal vision of the architect contributed to the production of modern architectures.Keywords: evolution of style; modernism; modern movement; post-colonial campus